Aníbal Mattos: Fomentador das Artes Plásticas na Belo Horizonte do início do século XX - Noronha, Claúdia Lima Ayer de; Rodrigues, Danielle Uchoa Alonso; Quiroga, Inês; Guimarães, João Ivo Dapieve Miranda Pinheiro Duarte; Hissa, Sarah de Barros Viana; Rodrigues, Raquel Silva (Temporalidades, 2010)
O mundo das artes plásticas na Belo Horizonte do início do século XX é usualmente caracterizado como essencialmente precário, tradicional e acadêmico. Esse artigo investiga esse momento e ambiente, focalizando a figura essencial de Aníbal Mattos e buscando averiguar a validade dessa caracterização recorrente. A atuação do fluminense Aníbal Mattos no fomento artístico e articulação do meio em Belo Horizonte foi decisiva, de modo que a ênfase do artigo envolve algo de sua abrangente trajetória pessoal e institucional nos meios intelectual e artstico da época. Mattos aparece como uma figura dinâmica e fundamental na integração dos artistas e interessados, por meio da promoção de exposições e instituições de ensino, ainda que efêmeras. A caracterização de Mattos como articulador de tal relevância lança dúvidas sobre certas determinações correntes acerca da atuação do artista frente a tentativas modernistas, assim como a tradicional dualidade entre academicismo e modernismo. Abstract: The world of plastic arts in Belo Horizonte in the early 20th century is typically characterised as inherently precarious, traditional and academic. This article investigates this period and environment, using as a focal point the essential figure of Aníbal Mattos, and questions the validity of this recurrent characterization. The authors assert that Mattos’ role in the incentivation and articulation of the artistic environment in Belo Horizonte was decisive, so much so that the emphases of this article also incorporates some observations of his personal and institutional trajectory in the intellectual and artistic environment of the time. Within this article it is argued that Mattos should be seen as a dynamic individual, fundamental to the integration of artists and other interested parties, by promoting exhibitions and education institutions, even if only short lived. This characterization of Mattos as an articulator of such relevance raises doubts concerning certain common assumptions about the artist’s actions towards the modernist movement, as well as the popularly perceived duality between academicism and modernism. Palavras chave: ANÍBAL MATTOS, ARTES PLÁSTICAS, BELO HORIZONTE. Keywords: ANÍBAL MATTOS, PLASTIC ARTS, BELO HORIZONTE.